THE USE OF ADVANCED SPACEBORNE THERMAL EMISSION AND REFLECTION RADIOMETER IMAGERY IN SOIL FERTILITY INVESTIGATION OF A FARMLAND IN ILE-IFE NIGERIA - Francis Omotayo Adekayode; Abdul-Rahman Adegbite; Rufus Olakunle Oladosu (European Scientific Journal, ESJ, 2013)
The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) image of a 350 hectare farmland in Ile-Ife (7033’N, 4033’E), Nigeria was processed to generate the contour and slope maps in a soil fertility investigation in 2012. The image Focal Statistics were generated using the Spatial Analyst/ Neighborhood/Focal Statistics Tools in ArcMap and the contour map generated at an interval of 5 m using the Spatial Analyst/ Surface/ Contour Tools while the slope map generated by using the Spatial Analyst/ Surface/ Slope Tools. Four slope classes of 0 to 2%, 2 to 4%, 4 to 6% and 6 to 8% were generated and soil samples taken from five sampling locations in each slope class for laboratory analyses for nitrogen, phosphorus, potassium and organic matter content. Surface interpolation for the generation of the spatial distribution of each of the nutrient concentrations was carried out with the 3D Analyst / Raster Interpolation / Kriging Tools while the overlay operation to generate the fertility classes were carried with the 3D/Raster Math Tools. Four fertility classes of low, medium, marginally good and good were mapped. The soil nutrient level of the greater part of the farmland was of medium to marginally good productivity classes while the percentage areas covered by low, medium, marginally good and good fertility classes were 11, 41, 39 and 9 % respectively.